Analisis Prioritas Kriteria Pemilihan Rumah Makan Padang oleh Mahasiswa Menggunakan Metode AHP dan SAW - Bagas Muhammad Priyambodo (Universitas Ma'arif Lampung, 2026)
This study aims to identify the most influential criteria affecting customer satisfaction and to evaluate Padang restaurant alternatives that best match students' preferences using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. Data were collected through a questionnaire administered to 380 students from the Faculty of Languages and Arts, Universitas Negeri Semarang (UNNES), who had previously visited Padang restaurants located around the campus. The analysis was conducted based on six main criteria: price, taste, distance, service quality, facilities, and cleanliness. The AHP results indicate that cleanliness (0.3508) and taste (0.3067) are the most influential factors in students' restaurant selection. The obtained Consistency Ratio (CR) of 0.094 confirms that the pairwise comparison matrix is sufficiently consistent. Furthermore, the SAW results corroborate the AHP findings by ranking cleanliness and taste as the highest-priority criteria, followed by service quality, distance, price, and facilities. These findings suggest that cleanliness and taste are the primary determinants influencing students' decisions when selecting Padang restaurants.